OPTIMALISASI TABUNGAN DOMESTIK INDONESIA MELALUI PENEKANAN LAJU TINGKAT KETERGANTUNGAN PENDUDUK - Putri Wulandari Atur Rejeki (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2013)
With Ordinary Least Square (OLS), the main purpose of this study is to analyze impact of young dependency ratio and old dependency ratio on the domestic saving in Indonesia. The data used in this study were data time series from 1980to 2009 obtained from Badan Pusat Statistik, Bank Indonesia, Nota Keuangan and World Bank. The result of this study shows that all of the dependency ratio simultaneously significant influence on the domestic saving and individually thedependency ratio significant influence on the domestic saving on Indonesia. Based on the value of elasticity and the level of significance of dependency ratio, the old dependency ratio plays a big role in influencing the domestic saving inIndonesia.